2015
DOI: 10.1037/neu0000151
|View full text |Cite
|
Sign up to set email alerts
|

Examining the frontal subcortical brain vulnerability hypothesis in children with neurofibromatosis type 1: Are T2-weighted hyperintensities related to executive dysfunction?

Abstract: T2-weighted hyperintensities, as they are currently measured, cannot be used as a strong indicator of executive dysfunction in children with NF1. Based on the available NF1 cognitive impairment pathogenesis models, a critical discussion on anatomical-functional relationships between hyperintensities and neuropsychological profile is proposed, especially the executive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 47 publications
7
28
2
3
Order By: Relevance
“…The latter would, however, be in conflict with a slight majority of studies that concluded that T2Hs associated with NF1 have a negative impact cognitive ability. [39][40][41][42] However, if the presence of T2Hs shows a high concordance within 11 NF1 MZ twin pairs as previously suggested, 12 it is debatable whether presence of T2Hs should be considered a nongenetic factor in the first place. Lastly, while allelic imbalance was observed in neurons derived from induced pluripotent stem cells of NF1 individuals and correlated with dopamine signaling, 19 our results collectively indicate that allelic imbalance is unlikely to add significantly to the variability of the cognitive NF1 phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…The latter would, however, be in conflict with a slight majority of studies that concluded that T2Hs associated with NF1 have a negative impact cognitive ability. [39][40][41][42] However, if the presence of T2Hs shows a high concordance within 11 NF1 MZ twin pairs as previously suggested, 12 it is debatable whether presence of T2Hs should be considered a nongenetic factor in the first place. Lastly, while allelic imbalance was observed in neurons derived from induced pluripotent stem cells of NF1 individuals and correlated with dopamine signaling, 19 our results collectively indicate that allelic imbalance is unlikely to add significantly to the variability of the cognitive NF1 phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Two articles reported additional interesting results related to T2H. Roy et al ( 34 ) found that the presence, number, size, or location of T2H lesions did not affect executive dysfunction in NF1 children. On the other hand, Piscitelli et al ( 35 ) found that patients with T2H in the cerebellum showed a lower IQ than patients without T2H in that brain location, possibly because of impaired visuospatial ability and language.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects with cerebellar UBOs (31 out of 49 NF1 children in the study) presented worse scores on verbal IQ, full-scale IQ and visuospatial tests (reasoning and memory) than subjects without cerebellar hyperintensities (18 out of 49 NF1 children in the study). However, Roy et al (33) showed no relationship between executive functions, evaluated with a test or a questionnaire, and the presence, number or location of T2-hyperintensities ( Table 2).…”
Section: Post 2010 Studies Morphologic Neuroimaging and The Relationsmentioning
confidence: 99%